Beware of Emigrants Bearing Gifts : Optimal Fiscal and Monetary Policy in the Presence of Remittances - Gapen, Michael (IMF Working Papers; Working Paper ;, 2006)
This paper uses a stochastic dynamic general equilibrium model to investigate the influence of countercyclical remittances on the conduct of fiscal and monetary policy and trace their effects on real and nominal variables in a business cycle setting. We show that remittances raise disposable income and consumption, and insure against income shocks, thereby raising household welfare. However, remittances increase the correlation between labor and output, thereby producing a more volatile business cycle and increasing output and labor market risk. Optimal monetary policy in the presence of remittances deviates from the Friedman rule, highlighting the need for independent government policy instruments.